Association of Systemic Inflammatory and Immune Indices With Survival in Canine Patients With Oral Melanoma, Treated With Experimental Immunotherapy Alone or Experimental Immunotherapy Plus Metronomic Chemotherapy - Garcia, Jéssica Soares; Nowosh, Victor; López, Rossana Verónica Mendoza; Massoco, Cristina de Oliveira (Frontiers in Veterinary Science, 2022)
Analysis of the expression of inflammatory markers before starting treatment in human patients with cancer helps to predict outcomes and prognosis; however, there have been few studies on this topic in veterinary medicine. The present study aimed to evaluate inflammatory indices before treatment with autologous antitumor vaccine alone or this vaccine plus metronomic chemotherapy (MC) to predict response and prognosis. The indices included the neutrophil–lymphocyte ratio (NRL), platelet–lymphocyte ratio (PLR), monocyte–lymphocyte ratio (MLR), systemic immune-inflammation index (SII), C-reactive-protein–albumin ratio (CRP/ALB), lactate dehydrogenase level (LDH), frequency of blood lymphocyte subsets (CD4+, CD8+, Treg, and CD4/CD8 ratio) and frequency of blood myeloid-derived suppressor cells (MDSCs: monocytic [M]- MDSCs, and granulocytic [PMN]-MDSCs). Blood samples were collected from 25 dogs with oral melanoma treated with the autologous antitumor vaccine and from nine dogs that received MC plus vaccine before surgery. There were no statistically significant differences in the progression-free survival (PFS) or overall survival (OS) between the groups. In addition to the clinical stage, the CRP/ALB ratio and blood circulating Tregs in the univariate analysis showed an association with PFS and OS, and thus were selected for multivariable analysis. The CRP/ALB ratio was associated with PFS [hazard ratio (HR), 1.1; 95% confidence interval (CI), 1.0–1.1; p = 0.017] and OS [HR, 1; 95%CI, 1.0–1.1; p = 0.023]. Similarly, Treg was associated with PFS (HR, 1.6; 95% CI, 1.2–2.1; p = 0.001) and OS (HR, 1.6; 95% CI, 1.2–2.1; p = 0.001). Furthermore, canine patients with a CRP/ALB ratio above the cut-off point of 1.9 (established by receiver operating characteristic curve analysis) had worse PFS and OS, indicating the impact of the preoperative CRP/ALB ratio on the PFS and OS of dogs with oral melanoma. The CRP/ALB ratio and frequency of circulating Tregs are potential prognostic markers in dogs with oral melanoma.